Book Launch: Political Economy and Policy Analysis (PEPA) Sourcebook - Mockshell, Jonathan; Resnick, Danielle (International Food Policy Research Institute, 2023)
Lead authors Jonathan Mockshell and Danielle Resnick presented these slides at the Virtual Book Launch of the Political Economy and Policy Analysis (PEPA) Sourcebook on October 10, 2023.